Dostoevsky in context - Martinsen, Deborah A.; Maĭorova, O. E. (Cambridge : Cambridge University Press, 2016)
This volume explores the Russia where the great writer, Fyodor Dostoevsky (1821-1881), was born and lived. It focuses not only on the Russia depicted in Dostoevsky's works, but also on the Russian life that he and his contemporaries experienced: on social practices and historical developments, political and cultural institutions, religious beliefs, ideological trends, artistic conventions and literary genres. Chapters by leading scholars illuminate this broad context, offer insights into Dostoevsky's reflections on his age, and examine the expression of those reflections in his writing. Each chapter investigates a specific context and suggests how we might understand Dostoevsky in relation to it. Since Russia took so much from Western Europe throughout the imperial period, the volume also locates the Russian experience within the context of Western thought and practices, thereby offering a multidimensional view of the unfolding drama of Russia versus the West in the nineteenth century.
Introduction: the many worlds of Dostoevsky / Olga Maiorova and Deborah Martinsen -- Social, historical, and cultural contexts. Changing political, economic, and social landscape ; The great reforms and the new courts / Richard Wortman ; The abolition of serfdom / Nathaniel Knight ; Punishment and crime / Anna Schur ; Socialism, utopia, and myth / James P. Scanlan ; Nihilism and terrorism / Derek Offord ; The'woman question', women's work, women's options / Barbara Engel ; The economy and the print market / Jonathan Paine -- Political, social, and cultural institutions. Russian monarchy and the people / Richard Wortman ; Empire / Olga Maiorova ; Service ranks / Irina Reyfman ; Education / Inessa Medzhibovskaya ; Science, technology, and medicine / Michael D. Gordin ; Jews, race, and biology / Harriet Murav ; Suicide / Susan Morrissey ; Children / Robin Feuer Miller ; Gambling / Richard J. Rosenthal -- Space and place. Symbolic geography / Anne Lounsbery ; St. Petersburg / Robert Belknap ; The crystal palace / Sarah J. Young -- Religion and modernity. Orthodox spirituality / Nel Grillaert ; Religious dissent / Irina Paert ; Roman Catholicism / Mikhail Dolbilov ; Islam / Robert Geraci -- Literature, journalism, and languages. Modern print culture / Konstantine Klioutchkine ; Realism / Liza Knapp ; Dostoevsky: translator and translated / Carol Apollonio ; Travel and travel writing / Susan Layton ; Folklore / Linda Ivanits ; Foreign languages / Karin Beck ; Theater / Maude Meisel ; Dostoevsky's journalism and fiction / Ellen Chances ; Dostoevsky's journalism in the 1860s / Sarah Hudspith ; Dostoevsky's journalism in the 1870s / Kate Holland ; Censorship / Irene Zohrab.
Title from publisher's bibliographic system (viewed on 01 Jan 2016).
Keywords: Dostoyevsky, Fyodor, -- 1821-1881 -- Criticism and interpretation; Dostoyevsky, Fyodor, -- 1821-1881 -- Themes, motives; Russia -- In literature